Morphological and sensory attributes of native cocoa, Bagua, Peru - Fernández Jeri, Armstrong Barnard; Chávez Quintana, Segundo; Julca Otiniano, Alberto; Vega Jiménez, Nancy (Journal of the University of Zulia, 2022)
This research was carried out with the objective of describing the morphological and sensory attributes of native cocoa in the Bagua province, Peru. It took place in the districts: Aramango, Copallín. El Parco, Imaza and La Peca. A population of 234 cocoa farms and a stratified sample of 70 farms were considered. Physicochemical characteristics were analyzed in the fruits (weight, length, diameter, grains, pH and ºBrix); sensory (basic flavors) and their descriptors (color, shape, basal constriction and apex). Main Component Analysis was used for the performance of the variables  The values for the fruit regarding weight and diameter were higher in La Peca and Aramango, respectively. The characteristics of the bean were predominantly sweet (more in La Peca) and with a length (> 1.2 cm) required to produce quality chocolates. The yellow color (88.6%), elliptical shape (80%) and absent basal constriction (71.4%) stood out in the fruit.